Kingdom of the Netherlands : Netherlands. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the Netherland's economic recovery has taken hold. Real growth is forecast to reach 3.1 percent in 2018 owing to robust domestic demand. Private consumption has been supported by rising disposable income and positive wealth effects from increasing housing prices. Net exports have proven resilient to global uncertainties, pushing up the already large current account surplus. Unemployment has continued to decline rapidly, although most of the jobs have been created under temporary contracts or self-employment status. The economy is expected to keep its momentum in the coming years. Domestic consumption and investment are forecast to remain the main drivers of growth, prompting a gradual decline of the current account surplus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet